Early childhood curriculum : planning, assessment, and implementation - McLachlan, Claire; Fleer, Marilyn; Edwards, Susan, 1975- (Cambridge University Press, 2013)
"In most countries, some form of curriculum has been designed by a government agency or the private sector. So why is it that the concept is so confusing and why is what is contained in the various curricula around the globe so different and highly contested? As Kiri said in the vignette, 'Surely the people who wrote those curriculum documents know what they are about?' Designing a curriculum document is a complex task and involves the use of a robust curriculum model which has been built upon a particular theoretical perspective. When you read through Chapter 2 you will be introduced to a range of curriculum theories and curriculum models. That chapter will help you as you think about and solve the issue of what is a curriculum document - at the macro level"--Resumé vydavatele
Terminologický slovník
Keywords: předškolní výchova; děti předškolního věku; kurikulum; výchova a vzdělávání; preschool education; preschool children; curriculum; education; monografie; monographs